Is psychotherapy a social anaesthetic? - Long, Wahbie (PINS-Psychology in Society, 2018)
[ B O O K R E V I E W ] Madsen, Ole Jacob (2014) The therapeutic turn: How psychology altered Western culture. London: Routledge. ISBN 978-1-138-01869-3 pbk. Pages viii + 194 Moloney, Paul (2013) The therapy industry: The irresistible rise of the talking cure, and why it doesn’t work. London: Pluto Press. ISBN 978-0-7453-2986-4 pbk. Pages 256 Ole Jacob Madsen’s The therapeutic turn and Paul Moloney’s The therapy industry offer arguments that, although different in their methods, draw the same conclusion – that mainstream psychology cannot account meaningfully for human subjectivity for as long as it continues to ignore social theory. Both books belong to a growing body of critical scholarship on psychopathology and psychotherapy, while going further than the standard reformist works such as Allen Frances’ Saving normal or Gary Greenberg’s The book of woe. Indeed, Madsen and Moloney’s interventions are not only empirical, they are clearly political. Their contributions are also eminently readable, their democratic, unencumbered prose in keeping with their progressive-radical values – which is more than one can say of the French poststructuralists and their special brand of slow torture.